2006
DOI: 10.1182/blood-2005-03-1306
|View full text |Cite
|
Sign up to set email alerts
|

T-cell non-Hodgkin lymphoma

Abstract: T-cell non-Hodgkin lymphomas (NHLs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(138 citation statements)
references
References 116 publications
6
122
2
8
Order By: Relevance
“…Angioimmunoblastic T-cell lymphoma (AITL) is one of the nodal peripheral T-cell lymphomas described in the WHO classification that accounts for 4-6% and 5% of all lymphomas in Western countries [1][2][3] and in Japan, 4 respectively. AITL typically presents with advanced stage disease, and is manifested by generalized lymphadenopathy, hepatosplenomegaly, and other systemic symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angioimmunoblastic T-cell lymphoma (AITL) is one of the nodal peripheral T-cell lymphomas described in the WHO classification that accounts for 4-6% and 5% of all lymphomas in Western countries [1][2][3] and in Japan, 4 respectively. AITL typically presents with advanced stage disease, and is manifested by generalized lymphadenopathy, hepatosplenomegaly, and other systemic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Patients exhibit immunodeficiency secondary to the neoplastic process. [1][2][3] In the majority of cases, expansion of B-cells positive for EpsteinBarr virus (EBV) is seen, which is thought to be a consequence of underlying immune dysfunction. 5,6 It has been reported that supervening EBV-associated B cell lymphoma can occur in AITL.…”
Section: Introductionmentioning
confidence: 99%
“…Certain histological subtypes have been noted to have a relative predilection site as mucosaassociated lymphoid tissue (MALT) lymphoma in stomach, mantle cell lymphoma (MCL) in terminal ileum, jejunum and colon, as well as enteropathyassociated T-cell lymphoma (EATL) in jejunum, and follicular lymphoma (FL) in duodenum with a geographic variation in its distribution. 21 Multifocality, however, has been noticed particularly in MALT lymphoma and follicular lymphoma. Certain risk factors have been implicated in the pathogenesis of gastrointestinal lymphoma including Helico-bacter pylori (H. pylori) infection, human immunodeficiency virus (HIV), celiac disease, Campylobacter jejuni (C. jejuni), Epstein-Barr virus (EBV), hepatitis B virus (HBV), human T-cell lymphotropic virus-1 (HTLV-1), inflammatory bowel disease and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…The more common types are peripheral T cell lymphoma and angioimmunoblastic T cell lymphoma. All may present with B symptoms, rash, lymphadenopathy, hepatosplenomegaly, hemolytic anemia, and thrombocytopenia (11).…”
Section: Malignancymentioning
confidence: 99%